An explorative study on I.T. and systems librarianship focusing on competencies, tasks, and responsibilities in the library setting - Cerdeno, Chris Gianni C.; Dorado, Dan Anthony D. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2014)
Since libraries are increasingly becoming more and more dependent on information systems and technologies in terms of their collection and services, a closer analysis on the position which caters to these aspects of library life have to be developed to incorporate IT and systems librarianship and pave the way for its establishment. In line with this, this study focused on the perceptions various experts and practitioners in the field regarding the profession.
Libraries were contacted to determine if there was/were a person/s fitting the description of an IT and systems librarian. They, and if applicable, their administrators, were the respondents of the survey and were asked questions regarding the various aspects of IT and systems librarianship according to their practical experience and/or expertise.
Among those examined were its origins and evolution, its role in the library, its tasks performed and responsibilities held, its necessity in the Philippine library, its benefits and disadvantages, its core competencies and the supplementary skills that go along with it, possible measures of productivity; and lastly its future, and the possibilities and potential that it has.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Systems librarians; Librarians -- Information technology -- Philippines